Islam, entrepreneurship, and embeddedness - Tok, M. Evren; Kaminski, Joseph Jon (Thunderbird International Business Review, 2019)
This study centers on the premise that entrepreneurship is an embedded process. Although "the entrepreneur" is inherently an "individual," entrepreneurship can never be fully disembedded from the more general social settings within which any business venture is situated. An Islamic‐based economic discursive framework should be cognizant of the different forms of sociality, spatiality, and community as well as the various norms, codes, and symbols that define society more generally. The work of Karl Polanyi on embeddedness is engaged and juxtaposed with Islam's understanding of the ideal mode of economic discursive practices. Islamic economic models and Polanyi are both critical of the corrosive effects of unbridled capitalism and individualism that ultimately lead to reification and exploitation. The conclusion recommends more small‐N case studies by researchers and entrepreneurial educational materials that emphasize the importance of networks and local embeddedness.
Keywords: Islam; POLANYI, Karl, 1886-1964; discursive practices; economic models; entrepreneurship; teacher researchers